2007
DOI: 10.1073/pnas.0707389104
|View full text |Cite
|
Sign up to set email alerts
|

Loss of skeletal muscle strength by ablation of the sarcoplasmic reticulum protein JP45

Abstract: Skeletal muscle constitutes Ϸ40% of the human body mass, and alterations in muscle mass and strength may result in physical disability. Therefore, the elucidation of the factors responsible for muscle force development is of paramount importance. Excitationcontraction coupling (ECC) is a process during which the skeletal muscle surface membrane is depolarized, causing a transient release of calcium from the sarcoplasmic reticulum that activates the contractile proteins. The ECC machinery is complex, and the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 47 publications
2
48
0
1
Order By: Relevance
“…12). While we have not determined the role of other triadic proteins such as JP-45 (12,55), the results of the current study offer circumstantial support that JP damage is involved in early force deficits due to EC coupling failure following the performance of eccentric contractions.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…12). While we have not determined the role of other triadic proteins such as JP-45 (12,55), the results of the current study offer circumstantial support that JP damage is involved in early force deficits due to EC coupling failure following the performance of eccentric contractions.…”
Section: Discussionsupporting
confidence: 38%
“…For example, JP-45 locates to the triad, binds to Cav1.1 in the T-tubule membrane and calsequestrin in the SR, appears to play a role in targeting Cav1.1 to the triad, and is required for normal EC coupling (2,3,12). On the basis of these characteristics, it is interesting to postulate that junctophilin and JP-45 damage consequent of performing eccentric contractions results in dissociation of Cav1.1 from RyR1 and then migration of Cav1.1 from the triad.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that increased Cavβ1a expression contributes to decreased Cav1.1 expression and muscle weakness with aging; however, the underlying mechanism is not gene transcription, because in young mice, Cav1.1 mRNA does not decline with Cavβ1a overexpression (Taylor et al ., 2009). We also demonstrated that JP45 regulates Cav1.1 expression through a mechanism independent of gene transcription (Delbono et al ., 2007, 2012). Aging skeletal muscle undergoes chronic denervation, but whether that accounts for the accumulation of nuclear TnCT remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle force was digitized at 4 kHz by using an AD Instruments converter. EDL tetanus was recorded in response to 350-ms pulses at 100 Hz as previously described (13). Specific force was normalized to the muscle cross-sectional area [CSA ϭ wet weight (18).…”
Section: Methodsmentioning
confidence: 99%